Lipase Enzyme Inhibitory Activity of Jombang Leaves Extract (Taraxacum officinale F.H. Wigg): Aktivitas Penghambatan Enzim Lipase Ekstrak Daun Jombang (Taraxacum officinale F.H. Wigg) Secara In Vitro - Muti, Annisa Farida; Adia, Risa; Rifkia, Via; Pradana, Dhigna Luthfiyani Citra (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2024)
Background: Obesity is a condition that occurs due to an imbalance between energy intake and expenditure. Lipase enzymes play an important role in the process of fat metabolism, making it a target in obesity treatment strategies. Jombang plant has been used for generations as an alternative treatment for various diseases. The main content of secondary metabolite compounds in jombang plants are phenolics, flavonoids, terpenoids, and alkaloids. Objective: This study was conducted to determine the activity and potential inhibition of jombang plant (Taraxacum officinale F.H. Wigg.) against lipase enzyme in vitro. Materials and Methods: The phytochemical screening was determined by a color change reaction with certain reagents, while total phenolic content was carried out using Folin-Ciocalteau reagent spectrophotometrically. The inhibitory activity of 96% ethanol extract of jombang leaves as well as orlistat as positive control was measured by titration method and using olive oil substrate. The extract concentrations used were 125 ppm, 250 ppm, and 500 ppm. Results: Jombang leaf extract contains alkaloid, phenolic, flavonoid and terpenoid compounds qualitatively. Determination of total phenolic content in 96% ethanol extract of jombang leaves was obtained at 12.69 Â± 0.91 mgGAE/g. The highest percentage of inhibition was found at a concentration of 500 ppm which amounted to 103.85%. The difference in the percentage of inhibition in all groups showed no significant difference (Sig>0.05). Conclusion: This study shows that jombang leaf extract is able to inhibit lipase enzyme activity with the highest percentage of inhibition was 103,85%.